If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + 12 = 4 Reorder the terms: 12 + 4n = 4 Solving 12 + 4n = 4 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 4n = 4 + -12 Combine like terms: 12 + -12 = 0 0 + 4n = 4 + -12 4n = 4 + -12 Combine like terms: 4 + -12 = -8 4n = -8 Divide each side by '4'. n = -2 Simplifying n = -2
| 26x+17=5(5x+3) | | Y=85x+2 | | -2x^2+x+21=0 | | z^2-18z=31 | | 10x+12y=43 | | 4x+3=3x+16 | | 6*a-11=13 | | 2.25+15=13.5t+14 | | 1+x=5x-9 | | -2(3y-5)-y=-4(y-2) | | y^2+18y+41=0 | | (4x^3+6x^2-8x)-(x^3-2x^2+12x)= | | 8x-2=8x-8 | | 7(y-4)+y=2(6+48) | | -2*-4=2 | | x/5=182² | | 48=9u-u | | P=1.85s+4.2f | | 2p-7=3p+4 | | r^2-30r=41 | | (-12+i)(8-4i)(-1+6i)=0 | | 5*x+8=23 | | a=0.008*150 | | k^2-28k-1=0 | | .5*16+x=16 | | 89-2x=65 | | 3(2j+6)=2(4b+1) | | 9-4p-3+p=36 | | q^2+18q=25 | | -5a-10+6=2+9a-3a+6 | | 32-x-25x=-43 | | (7v+3u-2)(v-7u)= |